Intriguing Near-Infrared Solid-State Luminescence of Binuclear Silver(I) Complexes Based on Pyridylphospholane Scaffolds - Shamsieva, Aliia V; Musina, Elvira I; Gerasimova, Tatiana P; Fayzullin, Robert R; Kolesnikov, Ilya E; Samigullina, Aida I; Katsyuba, Sergey A; Karasik, Andrey A; Sinyashin, Oleg G (Inorganic chemistry, 2019)
A series of novel charged disilver(I) complexes with pyridyl-containing phospholanes was synthesized. These complexes were characterized using a range of spectroscopic techniques and single-crystal and powder X-ray diffraction. The complexes demonstrate solid-state near-infrared (NIR) luminescence (765–902 nm) that is unique for dinuclear AgI complexes. Combined spectroscopic/quantum chemical analysis suggests that the NIR luminescence of complexes 4–6 in the solid state is mainly due to crystal packing effects.